A further review of European Magelonidae (Annelida), including descriptions of Magelona equilamellae and Magelona filiformis - Mortimer, Kate; Mills, Kimberley; Jordana, Esther; Pinedo, Susana; Gil, João (Zootaxa, 2020)
Following on from the partial review of European Magelonidae by Fiege et al. (2000), a dichotomous identification key, a table of characters and images of all nine known European magelonid species are provided. Magelona equilamellae is redescribed highlighting several features not reported originally by Harmelin. Notably the thoracic neuropodial lamellae, which are initially prechaetal but become distinctly postchaetal by chaetiger 7, an additional character allowing separation from the morphologically similar Magelona alleni. Records suggest that M. equilamellae is a Mediterranean species, more commonly occurring in shallow, transitional waters. Several new characters for Magelona filiformis are additionally highlighted as well as a number of corrections to the existing description, including the number of prostomial ridges, presence of abdominal lateral pouches, morphology of chaetiger 9, and the presence of smaller abdominal hooded hooks adjacent to lateral lamellae. The first image of M. filiformis minuta is provided, and its synonymy with M. filiformis further supported. corresponding email: Katie.Mortimer-Jones@museumwales.ac.uk
World Polychaeta Database (WPolyDb)